THE SELF-ASSESSMENT OF SUPERVISORS' SELF-CARE STRATEGIES - Lāce, Dace; Mārtinsone, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
During the COVID-19 pandemic, the availability of resources has decreased and the risk of burnout on employees increased. Supervision is one of the resources, available for employees to learn self-care. It was necessary to find out how supervisors themselves assessed self-care strategies. The aim of this study was to explore the self-assessment of Latvian supervisors' self-care strategies. The following research questions were raised: 1) What are the indicators of the importance and attainability of supervisors’ self-care strategies? 2) What are the difference indicators of the importance and attainability of supervisors’ self-care strategies? In this study importance is an assessment of how significant and necessary a certain value is, attainability is an assessment of how attainable a certain value is. Based on the Self-Care Strategies Questionnaire, an online survey was conducted between May and October of 2021. The respondents assessed the importance and attainability of their self-care activities using a four-point Likert scale. 66 supervisors participated in the survey. For data analysis the descriptive statistics and Wilcoxon signed-rank test were used. The results showed statistically significant differences between the self-assessment of importance and attainability in all strategies. The importance was rated higher than attainability. Planning of time, balance of personal and professional life, being alone and in silence, professional development, reading were the self-care strategies more often assessed higher and more often carried out by supervisors.